Pengaruh Pemberian Abon Belut (Monopterus Albus) dan Edukasi Gizi terhadap Kadar Hemoglobin Darah Penderita TB Paru - Riris Oppusunggu Penulis; Junita Lastari Girsang (POLTEKKES KEMENKES MEDAN, 2021)
This study aims to determine the effect of giving shredded eel and nutrition education to the Hb gadar of pulmonary TB patients in the working area of the Petumbukan Health Center, Deli Serdang Regency in 2019 for 30 days. This type of research is quasi-experimental, namely the design before and after the intervention using one group or called one group pre and post test design. The results showed that the value of p = 0.001. In conclusion, there is an effect of giving shredded eel and nutrition education on Hemoglobin Levels. Keywords: Shredded Eel, Education, Hemoglobin